2017
DOI: 10.1007/s00417-017-3663-4
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive measurements of the dynamic changes in the ciliary muscle, crystalline lens morphology, and anterior chamber during accommodation with a high-resolution OCT

Abstract: The ACD and ALRC decreased about 2 and 10 % per dioptre of accommodation, respectively; whereas the CLT and CMA increased about 2 and 9 %, respectively. These results add knowledge regarding the understanding of accommodation and give new perspectives for biomechanics and biometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…In our study, due to limitation of the OCT scan depth, we only analyzed changes at CM2 and CM3 and found that their thickness decreased after -6D accommodation stimulation. And our results are consistent with other studies 17,18 .…”
Section: Schlemm's Canal Changed In Different Accommodation States Ofsupporting
confidence: 94%
See 1 more Smart Citation
“…In our study, due to limitation of the OCT scan depth, we only analyzed changes at CM2 and CM3 and found that their thickness decreased after -6D accommodation stimulation. And our results are consistent with other studies 17,18 .…”
Section: Schlemm's Canal Changed In Different Accommodation States Ofsupporting
confidence: 94%
“…The change of CM provides direct evidence of accommodation stimulation and cycloplegia. There are researches which have explored changes in the ciliary muscle structure with accommodation using UBM, MRI and OCT [17][18][19][20][21] . The results indicate that the shape change occurred in the anterior portion of the ciliary muscle with accommodation.…”
Section: Schlemm's Canal Changed In Different Accommodation States Ofmentioning
confidence: 99%
“…Presbyopia is the age-related loss of accommodation [ 39 ]. Prior accommodation research utilized different modalities (OCT [ 16 , 21 , 22 , 24 , 25 , 30 , 32 , 40 ], ultrasound biomicroscopy [ 41 ], or MRI [ 42 , 43 ]) or variations of the same modality (combining different types of custom-built OCTs [ 23 , 44 ] to image different parts of the eye). Together, this precludes simultaneous assessment of all anterior segment anatomical alterations during accommodation before and after presbyopia, contributing to the challenge of understanding presbyopia pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to one of the main functions of the CM, accommodation, Esteve‐Taboada et al. () using a Visante OCT instrument found that crystalline lens thickness (CLT) and CMA went up by about 2% and 9%, respectively. Thus, the greater the accommodative effort, the larger the CMA, with median relative changes in 8.6%, 17.2% and 25.5% at 1, 2 and 3 D, respectively.…”
Section: Discussionmentioning
confidence: 99%